Results and Performance of the World Bank Group 2015 - Independent Evaluation Group (Washington, DC: World Bank, 2016)
The Independent Evaluation Group’s (IEG) Results and Performance of the World Bank Group (RAP) is a comprehensive assessment of World Bank Group performance, drawing on recent IEG evaluations. The report also examines how effectively the World Bank Group addressed current and emerging development challenges. This year’s RAP focuses on gender integration in World Bank Group operations, building on previous examinations of World Bank Group approaches to risk management (RAP 2013) and the Millennium Development Goals (RAP 2014).